Implementasi Pembelajaran Blended Learning di Program Studi Ilmu Komunikasi STKIP Agama Hindu Singaraja - I Putu Suarnaya; I Wayan Gara; I Dewa Gede Ngurah Diatmika; I Gede Andi Legawa; Ni Komang Ayu Meliantari; Made Suarnawa (Jayapangus Press, 2022)
A Hindu religious instructur, must be able to implement material and able to communicate well. This study aims to prioritize the implementation of learning with a blended learning model for Communication Science courses, and find the influence of the implementation of the blended learning approach on student learning achievement before and after with a blended learning model. The design of this study uses recycled Classroom Action Research, with the research subjects being students in the second semester of the 2020-2021 in Academic Year. The results of this study show that there is an optimization of the Implementation of the Blended Learning Model in the Communication Science Course in the Hindu Hindu Communication Studies Program STKIP Agama Hindu Singaraja. This can be seen from the average score of pre-test and post-test in cycle I and in cycle II. The average score of pretest in cycle I was 66.07 while the average score of posttest in cycle 1 was 68.93. From this data, it can be interpreted that there has been a significant increase but has not reached the average score target of 7.00. The results of the study in cycle II with an average pre-test score of 72.44 and a post-test score of 77.14. This can be interpreted as a significant increase and has exceeded the target achievement with an achievement score of 77.14. Based on the achievement of post test scores in cycles I and II, it has shown a significant increase from an average score of 68.93 to 77.14 with a gain score of 8.21.